2014
DOI: 10.1093/ajh/hpu225
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines and Reactive Oxygen Species as Mediators of Chronic Kidney Disease-Related Vascular Calcification

Abstract: This study demonstrates a relationship between inflammation/ROS and arterial calcification in CKD and contributes to understanding of the complex pathways that mediate arterial calcification in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 36 publications
5
130
0
1
Order By: Relevance
“…41 MMP-9 is secreted via inflammatory cells in the adventitia or smooth muscle cells. 42 In our study, a significant difference was found in the serum concentration of MMP-9 between nephrolithiasis patients and control group. Moreover, the significant increase was also found in the value of this biomarker within MMP-9/C1562T genotype T/T, TG and AG GG types in patients with nephrolithiasis.…”
Section: 35supporting
confidence: 44%
“…41 MMP-9 is secreted via inflammatory cells in the adventitia or smooth muscle cells. 42 In our study, a significant difference was found in the serum concentration of MMP-9 between nephrolithiasis patients and control group. Moreover, the significant increase was also found in the value of this biomarker within MMP-9/C1562T genotype T/T, TG and AG GG types in patients with nephrolithiasis.…”
Section: 35supporting
confidence: 44%
“…Phosphate up-regulates the expression of NOX4 and CYBA , two critical components of the superoxide-generating NADH/NADPH oxidase system [48, 49] and reduces total antioxidant capacity of VSMCs. Fibulin-3 supplementation is able to suppress the expression of NADH/NADPH oxidase system components and may, thus, interfere with reactive oxygen species production in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in CKD rat models, it was demonstrated that inflammation (TNF-␣, IL-1␤, IL-6) enhanced BMP2 and decreased SM ␣-actin expressions through activating MAPKs and phosphatidylinositol 3-kinase signaling pathways (2).…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 95%